Perspektif Sosial Ekonomi Penduduk Wilayah Pinggir Sungai Siak - Firman Nugroho (Universitas Riau, 2009)
This research to tittle to the social-economic community of Siak river a specialarea The collected of data is time series data from 2005-2007 years and methodology is survey. The result, condition for people's social-economic to shown: river and forest not support people's lives because destructed of rivers and forest;level of educated is low and high of droup out in education; degree of health andinfrastructur of health are low; the accesibility to financial in bank is low but'rentenir' support live peoples;Key words: droup-out, health, accessibility, 'rentenir',